Answer:
(x^2 + 3)(x + 1).
Step-by-step explanation:
x^3 + x^2 + 3x + 3
= x^2(x + 1) + 3(x + 1)
= (x^2 + 3)(x + 1).
Answer:
False
Step-by-step explanation:
Well to solve for z we single it out, distribute, use the communicative property, and combine like terms.
42 = -7(z - 3)42 = -7(z - 3)
Distribute
42 = -7z + 21*42 = -7z + 21
42 = -7z + 882 = -7z + 21
-42 to both sides
-7z + 840 = -7z + 21
-21 to both sides
-7z + 819 = -7z
+7z to both sides
819 = 0
<em>Thus, </em>
<em>the given equation is false.</em>
<em>I hope this helps :)</em>
1347.25 just easily divide to get your answer. Nothing else :)
Answer:
9
Step-by-step explanation:
40 -100 = 60 and 60 percent of 15 is 9
Answer:
y = (-1/2)x + 5
Step-by-step explanation:
As we move from the y-intercept (0, 5) to the x-intercept (10,0), x increases by 10 units while y decreases by 5 units. Thus, the slope of this line is
m = rise / run = -5 / 10 = -1/2.
Since we know both the slope and the y-intercept of this line, let's use the slope-intercept form of the equation of a straight line: y = mx + b.
Substituting -1/2 for m and 5 for b, we get:
y = (-1/2)x + 5